Utility of Nuclear Grading System in Epithelioid Malignant Pleural Mesothelioma in Biopsy-heavy Setting: An External Validation Study of 563 Cases. (March 2020) - Zhang, Yu Zhi; Brambilla, Cecilia; Molyneaux, Philip L.; Rice, Alexandra; Robertus, Jan L.; Jordan, Simon; Lim, Eric; Lang-Lazdunski, Loic; Begum, Sofina; Dusmet, Michael; Anikin, Vladimir; Beddow, Emma; et al.
Abstract : Nuclear grading systems for epithelioid malignant pleural mesothelioma (MPM) have been proposed but it remains uncertain if they could be applied in a biopsy-heavy setting. Using the proposed system, we conducted an independent, external validation study using 563 consecutive cases of epithelioid MPM diagnosed at our institution between 2003 and 2017, of which 87% of patients underwent biopsies only. The median number of sites sampled was 1, with a median maximum tissue dimension of 17 mm (biopsy) and 150 mm (resection). The median overall survival (OS) was 14.7 months. The frequencies of grade I, II, and III tumors were 31% (132/563), 52% (292/563), and 17% (94/563). Grade I tumors were associated with the most favorable median OS (24.7 mo) followed by grades II (12.7 mo) and III (7.2 mo). The 2-tier nuclear grade separated tumors into low grade (19.3 mo) and high grade (8.9 mo). In multivariate analysis, 3-tier nuclear grade, 2-tier nuclear grade, and mitosis-necrosis score predicted OS independent of age, procedural type, solid-predominant growth pattern, necrosis, and atypical mitosis (all P <0.001 except 2-tier nuclear grade, P =0.001). In the scenario of a single- site biopsy with tissue dimension ⩽10 mm, none but age ( P =0.002) were independently predictive. Our data also suggested sampling 3 sites or a maximum tissue dimension of at least 20 mm from a single site is optimal for nuclear grade assessment. In conclusion our study confirmed the utility of nuclear grade in epithelioid MPM using a biopsy-heavy cohort provided the tissue sample met minimum dimensional criteria. Abstract : Supplemental Digital Content is available in the text.